Quality Improvement Management in Teacher Professional Development - Isa, Muhammad; Neliwati, Neliwati; Hadijaya, Yusuf (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This research aims to evaluate the professional competence of elementary school teachers in Binjai City and the effectiveness of teacher quality management programs and related initiatives in raising teacher competency levels. The term for this kind of study is qualitative descriptive research, and it is a way of gathering information about the people and events studied via written or spoken descriptions. It is based on the individual's background as a whole (holistic) rather than isolating the individual and the organization into variables and examining them. in the context of the whole. Reading various written materials, looking at images, pondering about items, seeing individuals in their immediate environment via interviews, and other activities are all part of the qualitative research design. Qualitative methods are used in this study to obtain data. Researchers often use observation, document analysis, and interviewing in qualitative research as data collection methods. The study's findings demonstrate (1) That the Binjai City Public Elementary School instructors are qualified educators. The quality of instructional materials is correlated with the professionalism of teachers. Professional instructors construct high-quality education or learning processes for students to enjoy participating in the learning process and for school graduates to develop human resources of the highest caliber. (2) In general, educators at Binjai City Public Elementary Schools use a variety of instructional strategies, such as technology-based learning and cooperative learning. (3) Although cooperative learning and technology-based learning are the two learning methodologies that educators constantly use to carry out the teaching and learning process, many Binjai City Public Elementary School instructors have certifications and pursue further education.